Are radiological joint space widths of normal hips asymmetrical?. Issue 4 (1st April 1999) - Reis, Paulo; Nahal-Said, Roula; Ravaud, Philippe; Dougados, Maxime; Amor, Bernard
Abstract : BACKGROUND: To be certain that the joint space width is abnormal in the case of hip joint pain when compared with the contralateral hip requires knowledge of physiological dissymmetry. AIM OF THE STUDY: To assess interindividual variability and dissymmetry in pelvic radiological joint space width. METHODS: Pelvic radiographs of subjects without hip joint disease. Measurement with a 0.1 mm graduated magnifying glass and 0.5 mm graduated flat ruler at the hip superointermediate site (vertical going through the femoral head centre). After randomisation of the side to measure, analysis of nine groups of 19 plain films by one investigator blind for the result of the contralateral side. RESULTS: The difference between the left and right hip was plotted against the corresponding mean for all 171 normal subjects This shows the frequency and the limits of the asymmetry at each measurement site. The asymmetry is independent of interindividual variability of the joint space width and greater than the measurement error in most subjects. CONCLUSION: This study confirms the interindividual variability of hip joint space width, shows the frequency of hip joint space asymmetry and defines its limit.